Putting Lifeworlds at Sea: Studying Meaning-Making in Marine Research - Siriwardane-de Zoysa, Rapti; Hornidge, Anna-Katharina (Frontiers in Marine Science, 2016)
An individual's “lifeworld” guides perceptions, the attachment of meaning and in sum, the interpretation of reality in everyday life. Yet the lifeworld (Ger. Lebenswelt) has been an undertheorized concept within interdisciplinary marine research. Through a two-stage analysis, we critically engage with the philosophical foundations, heuristic value and the methodological versatility that the interpretivist concept of the lifeworld stands to offer, drawing from contemporary marine scholarship. With two illustrative case studies exploring the lived realities of vastly different waterworlds in rural Uzbekistan and Sri Lanka, we further engage with the strengths and limitations of integrating a lifeworlds analysis into interdisciplinary work on localized perceptions. As a second step, we analyze the efficacy of adopting a phenomenological-lifeworlds approach in order to inductively explore diverse realities of coastal and sea-based peoples, while acknowledging the terrestrially-bound and anthropocentric genesis of the lifeworld as a concept. Therefore, in order to enliven hybrid thematic currents, conceptual debates and methodologies on “marine lifeworlds” on its own terms, we propose two thematic vantage points for interdisciplinary intervention by: (a) critically engaging with cognitive-material meanings and lived interpretations of “saltwater” realities; (b) tracing multiple modes of sociality and being with/in-the-world that go beyond human entanglements. In sum, we argue that while the lifeworlds concept affords spaces through which to study the complexities and ambivalences rife in surface-level perceptions, it promises the means with which to sidestep over-simplistic inferences to the vague and embattled notion of “culture,” while widening horizons for reflective and experimental-experiential lines of inquiry.